Encephalopathy, deafness and blindness in young women: a distinct retinocochleocerebral arteriolopathy?. Issue 1 (January 1989) - Bogousslavsky, J; Gaio, J M; Caplan, L R; Regli, F; Hommel, M; Hedges, T R; Ferrazzini, M; Pollak, P
Abstract : Three young women (aged 18 years, 19 years and 19 years) who developed progressive neuropsychic and neurologic disturbances with hearing loss and multifocal retinal artery branch occlusions are reported. This retinocochleocerebral syndrome has been reported previously only in 12 young North American women. Its pathogenesis is unknown, but an atypical viral infection of the vessel walls has been suggested. Abnormalities of T lymphocytes subsets in blood in one of the patients suggested an immunological dysfunction, but all other tests, including immunological reactions on brain and skin biopsies, were negative or non-specific. Steroids and immunosuppressive agents have been advocated on an empirical basis, but the second patient showed a substantial recovery without any therapy and the third gradually deteriorated despite azathioprine, cyclophosphamide, prednisone and plasma exchanges. This retinocochleocerebral syndrome probably corresponds to an arteriolopathy of unknown nature.